Noise pollution limits metal bioaccumulation and growth rate in a filter feeder, the Pacific oyster Magallana gigas - Charifi, Mohcine; Miserazzi, Alison; Sow, Mohamedou; Perrigault, Mickael; Gonzalez, Patrice; Ciret, Pierre; Benomar, Soumaya; Massabuau, Jean-Charles (PLOS ONE, 2018)
Shipping has increased dramatically in recent decades and oysters can hear them. We studied the interaction between noise pollution and trace metal contamination in the oyster Magallana gigas. Four oyster-groups were studied during a 14-day exposure period. Two were exposed to cadmium in the presence of cargo ship-noise ([Cd++]w ≈ 0.5 μg∙L-1; maximum sound pressure level 150 dBrms re 1 μPa), and 2 were exposed only to cadmium. The Cd concentration in the gills ([Cd]g) and the digestive gland ([Cd]dg), the valve closure duration, number of valve closures and circadian distribution of opening and closure, the daily shell growth-rate and the expression of 19 genes in the gills were studied. Oysters exposed to Cd in the presence of cargo ship-noise accumulated 2.5 times less Cd in their gills than did the controls without ship noise and their growth rate was 2.6 times slower. In the presence of ship noise, oysters were closed more during the daytime, and their daily valve activity was reduced. Changes in gene activity in the gills were observed in 7 genes when the Cd was associated with the ship noise. In the absence of ship noise, a change in expression was measured in 4 genes. We conclude that chronic exposure to cargo ship noise has a depressant effect on the activity in oysters, including on the volume of the water flowing over their gills (Vw). In turn, a decrease in the Vw and valve-opening duration limited metal exposure and uptake by the gills but also limited food uptake. This latter conclusion would explain the slowing observed in the fat metabolism and growth rate. Thus, we propose that cargo ship noise exposure could protect against metal bioaccumulation and affect the growth rate. This latter conclusion points towards a potential risk in terms of ecosystem productivity.